Rapid propagation in vitro and accumulation of active substances of endangered Dendrobium cariniferum Rchb. f. Issue 1 (1st January 2020) - Lin, Wei; Wang, Jingjing; Xu, Xiuming; Wu, Yuhan; Qiu, Dongliang; He, Bizhu; Sarsaiya, Surendra; Ma, Xiaokai; Chen, Jishuang
ABSTRACT: Dendrobium cariniferum is a valuable ornamental and medicinal plant rich with polysaccharides, alkaloid, and other bioactive compounds, which are potential raw materials for pharmacological utilization. In this study, an efficient protocol for the rapid propagation of D. cariniferum was developed. By using the tissue culture protocol, the effects of pH, hormone combinations, temperatures, light intensity, culture time protocorm proliferation, seedlings rooting, and accumulation of biomass with bioactive compounds were investigated. The experiments showed that the medium [1/2 MS + activated carbon1.0 g/L+ agar strip 7.5 g/L + sucrose 25 g/L] effectively promoted the germination of D. cariniferum seeds. The optimal culture conditions were found at pH 5.7, temperature 23 ± 2°C, and light intensity of 1000 Lx in the protocorm proliferation stage. Adding 1.5 g/L peptone in the medium effectively promoted the seedling rooting. The optimal culture conditions for accumulation of bioactive compounds (polysaccharides and alkaloids) of seedlings were found at temperature of 25 ± 2°C, light intensity of 1500–2000 Lx after the 60-day (d). Our study constructed a rapid propagation system in vitro for D. cariniferum, as well as the methods for efficient accumulation of active substances in seedling culture, which will serve as guidance for industrial production of D. cariniferum seedlings for both medicinal raw materials and ornamental plants. In addition, our study provided a new idea that we can directly use the high bioactive compound seedlings to extract medicinal components in industry conditions without transferring to the field. Graphical abstract: